CASE STUDIES IN LARGE-SCALE ARCHAEOLOGICAL SITE CONSERVATION AND MANAGEMENT IN CHINA: THE LIANGZHU, YIN XU, AND HAN YANGLING SITES - Wang, Dongdong; Nakamura, Shin’ichi (História: Questões e Debates, 2018)
Conservation of what are termed large-scale archaeological sites in China has been undertaken since the turn of the twenty-first century due to increasing threats posed by natural disasters and urbanization, as well as the needs to display and utilize these archaeological sites. Changing administrative structures and new approaches to conserving and utilizing large-scale sites are attempting to address these threats and needs. This paper presents a classification of these large-scale sites, as well as three typical cases for a detailed discussion. Using published literature and field surveys, this study addresses two main issues. The first issue is how governmental agencies adjust current organizations and mechanisms in order to satisfy the social, ecological, and economic requirements of a project. The second issue is how governmental agencies identify the responsibilities of different stakeholders in relation to the conservation of archaeological sites within the context of local development.